LITERATURE REVIEW: THE INFLUENCE OF SOCIAL MEDIA MARKETING ON CONSUMER BEHAVIOR - Anita Rahmawati; Sri Isti Untari; Kristin Lukitaningrum; Genesa Vernanda; Eva Fitria (Journal of Accounting Research, Utility Finance and Digital Assets, 2026)
The development of digital technology has transformed conventional marketing communication patterns from conventional methods to a more interactive, social media-based approach. Social media marketing (SMM) has become one of the key strategies for companies in building relationships with consumers and influencing purchasing behavior. This study aims to examine the influence of social media marketing on consumer behavior through a literature review approach. The method used is a Systematic Literature Review (SLR), analyzing various accredited national journals and relevant international literature in the fields of digital marketing and consumer behavior. The findings indicate that social media marketing has a significant influence on consumer behavior through several key mechanisms, namely increased brand awareness, electronic word of mouth (e-WOM), and customer engagement. These three variables act as mediators that strengthen the relationship between social media marketing and consumer purchasing decisions. Furthermore, it was found that consumer behavior in the digital age is more complex as it is influenced by social interactions, digital content, and recommendations from other users on social media. This study concludes that social media marketing not only has a direct influence but also operates through psychological and social processes that shape consumer purchasing decisions. This study makes a theoretical contribution to the development of the digital marketing literature and offers practical implications for companies seeking to design more effective social media marketing strategies.